Художньо-естетична парадигма роману у віршах «Мамай» Леоніда Горлача - Біляцька, В. П. (My University, 2018)
У статті розглянуто роман у віршах Л. Горлача «Мамай» – історичний (визначення автора), химерний (наше уточнення), у якому легендарний козак-характерник є втіленням феномену національної пам’яті. У дослідженні акцентовано на широкій панорамі життя минулих віків та сучасного українського суспільства, авторській рецепції дійсності, історизмі роману у віршах, аспектах художньо-естетичної парадигми, химерності як жанрово-стильової домінанти.

The article deals with one of the three novels in verse about kozak Mamay, legendary sorcerer who embodies the phenomenon of national memory – historical (author’s identification), chimeric (our specification) «Mamay» by Leonid Horlatch. It does not accent on a broad panorama of the past centuries life and modern Ukrainian society, author’s reception of reality or historical historicism of novel in verse, but it highlights the aspects of artistic and aesthetic paradigm and whimsicality as genre and stylistic dominant.
Keywords: роману у віршах; Мамай; химерність; реальність; фольклорність; жанр; Леонід Горлач; novel in verse; Mamay; whimsicality; reality; folklore; genre; Leonid Horlatch